Employees performance evaluation : A Malaysian case - Rusli, Ahmad (RS Publishing, 2012)
This book offers a research base knowledge and research findings to study employees' appraisal. It is hoped this edited books can help university student, government officer, human resource practitioner, policy maker, and all those who are really keen to know about employees' appraisal. This book will offer a good understanding of the performance appraisal issue in the Malaysian prespectives. It is hopes the readers will gain a lot of benefit from the knowledge offer. Research or indepth study also can be carried out by others researcher to give better understanding and explaination on the performance appraisal issues.